1999
DOI: 10.1016/s1044-0305(98)00157-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanoelectrospray—More than just a minimized-flow electrospray ionization source

Abstract: The comparison between electrospray ionization (ESI) mass spectra from NaCl solutions with and without analyte obtained under ionspray and nanospray conditions reveals different mass spectral behavior of the two ESI techniques. This can be attributed to the different initial droplet sizes which are in the microns range for ionspray, while in nanospray they are believed to be about one order of magnitude smaller. In the context of the widely accepted uneven-fission model, nanospray would then enter one fission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
377
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(390 citation statements)
references
References 22 publications
11
377
2
Order By: Relevance
“…Consistent with recent observations [48], very similar charge state distributions were obtained for nanoESI and regular ESI. However, salt adduction was less pronounced for nanoESI [32,41,42]. TWIMS profiles acquired under gentle conditions display well-resolved maxima, corresponding to Ω values of 986 Å 2 for Ubq, 1351 Å 2 for Cyt, 1782 Å 2 for hMb, and 4552 Å 2 for Hb (Figure 4).…”
Section: Twims Of Native Proteins Using Regular Esi and Nanoesimentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with recent observations [48], very similar charge state distributions were obtained for nanoESI and regular ESI. However, salt adduction was less pronounced for nanoESI [32,41,42]. TWIMS profiles acquired under gentle conditions display well-resolved maxima, corresponding to Ω values of 986 Å 2 for Ubq, 1351 Å 2 for Cyt, 1782 Å 2 for hMb, and 4552 Å 2 for Hb (Figure 4).…”
Section: Twims Of Native Proteins Using Regular Esi and Nanoesimentioning
confidence: 99%
“…(2) NanoESI operates with capillaries that have a much narrower outlet, giving rise to smaller initial droplets, and flow rates less than 100 nL min -1 [2]. Advantages of nanoESI include improved desolvation, greater salt tolerance, and higher ion yield [32,41,42]. However, nanoESI tends to be less robust in terms of signal stability and reproducibility than regular ESI [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…It has been stated that nanospray, a lowflow subclass of ESI, is even softer [6,7] and has a greater tolerance for non-volatile salts [8] than conventional electrospray, thereby making it even more suitable for the study of non-covalent interactions. There are now a number of reports that detail the observation of non-covalent interactions using mass spectrometry, and this topic has been recently reviewed by several groups [9 -13].…”
mentioning
confidence: 99%
“…However, extensive dissociation during ESI is also observed for some electrostatically stabilized complexes, even under the most gentle ionization conditions [34]. ESI-MS can also produce false-positive results, i.e., some analytes tend to form noncovalent gas-phase assemblies during ESI, despite the nonexistence of the corresponding complexes in solution [35,36]. Hu et al have demonstrated that the nonspecific binding of metal ions to proteins can be a severe problem when the ionization conditions are not chosen properly [37].…”
mentioning
confidence: 99%